A case of dementia with Lewy bodies with psychosis induced by low-dose gabapentinoids - Hideki Kanemoto; Taisuke Akiyama; Daiki Taomoto; Manabu Ikeda (BMC Psychiatry)
Abstract Background Hypersensitivity to antipsychotic drugs is one of the supportive features of dementia with Lewy bodies, and side effects to drugs other than antipsychotics are also known to occur frequently. We experienced a case of dementia with Lewy bodies in which hallucinations and delusions repeatedly appeared and disappeared after administration and discontinuation of mirogabalin and pregabalin. Case presentation The patient, a woman in her late 70s, developed hallucinations and delusional misidentification of places and persons immediately after receiving a prescription of mirogabalin (15 mg daily) for neuropathic pain. After discontinuation of mirogabalin, her hallucinatory delusions improved but remained. Mild dementia and mild parkinsonism were associated, cognitive fluctuations were evident, and dopamine-transporter scintigraphy showed bilateral striatal uptake reduction. Residual psychosis resolved with donepezil. Later, when the pain worsened, pregabalin (25 mg daily) was administered, and the psychosis recurred and resolved with discontinuation. Conclusions Although pregabalin-induced psychosis has been reported at higher doses (300–450 mg daily), it has not been reported at doses as low as those used in this patient. Gabapentinoids may cause psychosis in patients with dementia with Lewy bodies even at low doses, likely due to hypersensitivity to gabapentinoids in DLB.